RESTORATIVE JUSTICE AS AN ALTERNATIVE APPROACH TO PROTECTING CHILDREN IN CONFLICT WITH THE LAW - Rajarif Syah Akbar Simatupang (NOMOI Law Review, 2026)
This study aims to analyze the regulation and implementation of restorative justice in protecting children in conflict with the law in Indonesia, and to identify gaps between legal norms and practice in the field. The method used is a normative juridical approach with a statutory and conceptual approach, supported by an analysis of the empirical practice of diversion implementation. The results of the study indicate that restorative justice has been normatively accommodated in the juvenile criminal justice system, particularly through the diversion mechanism, which must be pursued at every stage of the judicial process. This approach reflects a paradigm shift from retributive justice to restorative justice, which emphasizes recovery, perpetrator responsibility, and victim and community participation. However, its implementation still faces various obstacles, including regulatory disharmony, inconsistent implementation among law enforcement agencies, limited human resource capacity, and a lack of supporting infrastructure. Furthermore, the dominance of a retributive legal culture and suboptimal protection for victims also weaken the effectiveness of this approach. Nevertheless, the practice of diversion demonstrates that restorative justice has significant potential in realizing a more humane and equitable juvenile criminal justice system. Therefore, comprehensive efforts are needed to optimize its sustainable implementation.